1993
DOI: 10.1002/em.2850210208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methyl methanesulfonate on mouse sperm chromatin structure and testicular cell kinetics

Abstract: Effects of methyl methanesulfonate (MMS) on mouse testicular cell kinetics and sperm chromatin structure were determined flow cytometrically. Mice were exposed to a single ip injection of saline containing 0 or 150 mg/kg MMS. Relative ratios of 1N, 2N and 4N testicular cells were not affected until 22 days postexposure. Ratios of 1N cell types were altered from 13 to 22 days and were near normal by 25 days. This study revealed an MMS induced alteration of chromatin structure in testicular, elongated spermatids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Several alkylating agents, including ethylnitrosourea, methyl methanesulphonate, thiotepa and triethylenemelamine, have been reported to result in sperm chromatin structural changes, as measured by flow cytometry (Evenson et al, 1985;Evenson et al, 1986;Evenson et al, 1989;Evenson et al, 1993). In the present study, the SCSA w /AO DNA denaturation assay revealed significant epididymal sperm nuclear structural effects of CPA exposure; maximal changes occurred in mid-spermiogenic elongating spermatids.…”
Section: Discussionsupporting
confidence: 48%
“…Several alkylating agents, including ethylnitrosourea, methyl methanesulphonate, thiotepa and triethylenemelamine, have been reported to result in sperm chromatin structural changes, as measured by flow cytometry (Evenson et al, 1985;Evenson et al, 1986;Evenson et al, 1989;Evenson et al, 1993). In the present study, the SCSA w /AO DNA denaturation assay revealed significant epididymal sperm nuclear structural effects of CPA exposure; maximal changes occurred in mid-spermiogenic elongating spermatids.…”
Section: Discussionsupporting
confidence: 48%
“…Sperm residing longer in the male reproductive tract can experience higher exposures to oxidative stress (49), but the implications for male infertility and heritable mutations are likely to be complex. Several studies have suggested that high levels of oxidative stress may render sperm incapable of fertilization, whereas others have suggested that sperm exposed to oxidative stress remain capable (49,50). Exposure to oxidative stress can induce DNA strand damage and breaks in both somatic and germ cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…Further research will indicate whether these different tests will detect other factors that may be significant for pregnancy outcome. Other studies on rodents that have used the same sperm samples known to have DNA strand breaks have confirmed a high level of DNA denaturation (Estop et al, 1993;Evenson et al, 1993b). Currently, the previous single COMP␣ t population has been replaced by percentage spermatozoa with non-detectable (formerly the main population) and detectable (moderate and high populations) DFI.…”
Section: Data Analysis-new Terminologymentioning
confidence: 98%